U.S. multinationals and preferential market access - Emily Blanchard; Xenia Matschke (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper examines the relationship between offshoring activity by U.S. multinational firms and the structure of U.S trade preferences. We combine firm level panel data on U.S. foreign affiliate activity from the U.S. Bureau of Economic Analysis (BEA) with detailed measures of U.S. trade preferences from the U.S. International Trade Commission (USITC) to create a three-way panel that spans 80 industries, 184 countries, and ten years (1997-2006). Consistent with existing theory, we find that offshoring multinational activity and preferential market access are positively and consistently correlated, both in the pooled sample and within countries, industries, and years. Using both instrumental variables and simultaneous equations approaches to address the likely endogeneity of export-oriented foreign investment, we find that each 1 billion in U.S. foreign affiliate exports to the U.S. from a particular industry and country is associated with roughly a 3.5 percentage point increase in the rate of preferential duty free access. Restricting attention to the Generalized System of Preferences (GSP), the dollar-for-dollar influence of multinational affiliate sales on preferential market access declines by roughly a third for the overall sample, but rises by more than an order of magnitude when we restrict attention to potentially GSP eligible countries.
Keywords: F13; F15; F21; F23; 330; Multinationales Unternehmen; Auslandsverlagerung; Zollpräferenz; USA